Caricom's trade : a quick reference to some summary data 1980-1996 (CCS GeorgetownGY, 1998)
Presents some of the basic summary trade data to which users frequently refer and focuses primarily on Caricom's trade with principle trading partners, as well as on intra-CARICOM trade.
DC